IMPLEMENTASI PERATURAN DAERAH NO. 39 TAHUN 2006 TENTANG PENERTIBAN HEWAN LEPAS DI KABUPATEN BONE BOLANGO - Rachmad Tahir , Muhammad; Hamzah, Suleman; Sahabat, Andi Inar (Fakultas Hukum Universitas Muhammadiyah Palu, 2024)
This research aims to find out how Regional Regulation No. 39 of 2006 concerning Controlling Loose Animals in Bone Bolango Regency and to find out what factors hinder the implementation of Regional Regulation No. 39 of 2006 concerning Controlling Loose Animals in Bone Bolango Regency, such as their types. This research is descriptive in nature which aims to accurately describe the characteristics of an individual, condition, symptom or to determine whether there is a relationship between a symptom or determine whether there is a relationship between another symptom in society. Based on the research results, in implementing Regional Regulation no. 39 of 2006 concerning Controlling Loose Animals in Bone Bolango Regency has not gone as expected because there are still several things that make this regional regulation not optimal, some of which are the causes of inappropriate achievement of goals, imposition of targets, time, making choices, and determination in measurements, from The Regional Regulation enforcement agency is the Bone Bolango Regency Civil Service Police Unit. This is indicated by the lack of special facilities for livestock from the government and if we look at it from the public, in principle they don't know about this Regional Regulation, which causes many animals to just run loose, considering that the impact of animal harm is not too fatal, as well as the lack of special facilities and budget from the government. as well as relaxing the special socialization of regional regulation no. 39 of 2006 concerning Controlling Loose Animals.